Studi Kualitatif Tentang Keterampilan Kolaborasi Siswa Dalam Pembelajaran IPS Kelas IV di Sekolah Dasar - Wella Puspita Dewi; Leny Julia Lingga (Jayapangus Press, 2025)
Collaborative skills are an essential competency that needs to be developed in Social Studies (IPS) learning; however, in practice, some students are still unable to work together optimally during group activities. This study aims to identify the collaborative skills of fourth-grade students at SD 005 Selunak as demonstrated during the IPS learning process. This research employed a descriptive qualitative method, with data collected through interview sheets, observation sheets, and documentation review. The subjects of this study were the fourth-grade teacher and students of SD 005 Selunak. Data analysis was conducted using the Miles & Huberman model, which consists of three stages: data reduction, data display, and conclusion drawing. The results show that students’ collaborative skills have begun to develop through group activities, as indicated by active interactions among group members, relatively clear task distribution, attempts to resolve minor conflicts, shared decision-making, and attitudes of mutual support and respect. Nevertheless, some students still require guidance to participate more actively and assume roles more proportionately. In conclusion, students’ collaborative skills are evident in IPS learning, but they still need to be strengthened through continuous practice, teacher guidance, and more structured activity design.